2007
DOI: 10.1088/1751-8113/40/10/005
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in a lattice population model

Abstract: We introduce a model for a population on a lattice with diffusion and birth/death according to 2A −→ 3A and A −→ φ for a particle A. We find that the model displays a phase transition from an active to an absorbing state which is continuous in 1 + 1 dimensions and of first-order in higher dimensions in agreement with the mean field equation. For the 1 + 1 dimensional case, we examine the critical exponents and a scaling function for the survival probability and show that it belongs to the universality class of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…From our mean field analysis, we therefore have a phase diagram as shown in figure 2. We note that in our earlier paper [12], we examined the case k = 0 and so were restricted, at the mean field level, to the first-order regime only.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…From our mean field analysis, we therefore have a phase diagram as shown in figure 2. We note that in our earlier paper [12], we examined the case k = 0 and so were restricted, at the mean field level, to the first-order regime only.…”
Section: The Modelmentioning
confidence: 99%
“…To find the values of p d c in the first-order regime we adopt an approach inspired by Lee and Kosterlitz [15] (see also [12]), due to the lack of power-law behaviour. For k < k * we examine Plots showing the critical behaviour of the model through powerlaw behaviour for the continuous phase transitions (k k * ) and a histogram of population density for the first-order transitions (k < k * ).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the model displays a phase transition from an active to an absorbing state which is continuous in 1 + 1 dimensions and of first-order in higher dimensions [1]. They also investigated the importance of fluctuations and that of the population density, particularly with respect to Allee effects in regular lattices [2].…”
mentioning
confidence: 99%
“…For most real networks, the connectivity distribution has powerlaw tails P (k) ∼ k −γ , namely, a characteristic value for the degrees is absent, hence the scale-free (SF) property. In this Brief Report, we shall study the simple RD population model [1] on SF networks.…”
mentioning
confidence: 99%